Hubungan antara Pengetahuan dan Paparan Media Massa dengan Perilaku Pacaran Remaja - H. R., Robi'i Pahlawan; Wijayanti, Anisa Catur (Universitas Ahmad Dahlan, 2018)
Background: Teenagers are a labile phase where it is very easy to be influenced by things from the outside whether it is a good thing or a bad thing. Teenager’s sexual behavior is influenced by risky courtship behavior. The impact of risky dating behavior is unwanted pregnancy, to be unsocialized and psychological disturbance. Kartasura District is the region with the highest number of Sexusl Transmission Infections (STIs) and Acquired Immunodeficiency Syndrome (AIDS) in Sukoharjo District. Method: This research was an analytic research with crossecttional approach and using quota sampling. The population in this study was all teenagers aged 10-19 years in Kartasura District and 120 teenagers as the sample of the research. Results: The result of bivariate analysis between knowledge and dating behavior got p value= 0,024> 0,05, and correlation between exposure of mass media to teen’s courtship behavior got p value= 0,000<0,05. Conclusion: Based on the results of the data analysis using chi square, it is known that there is a correlation between knowledge (p value= 0,024) and mass media exposure (p value= 0,000) with teenage dating behavior in Kartasura district.